Timely laparoscopic intervention for ovarian tumor-related autoimmune encephalitis: A challenging pathology at Tu Du Hospital in Vietnam and literature review - Thanh Hai Pham; Phuc Nhon Nguyen; Quang Nhat Ho (Wolters Kluwer Medknow Publications, 2023)
A previously fit and healthy 39-year-old woman was admitted to our tertiary referral hospital with coexisting autoimmune encephalopathy and ovarian tumor. Due to the presence of anti-N-methyl-d-aspartate receptor (anti-NMDAR) in the cerebrospinal fluid, a diagnosis of anti-NMDAR encephalitis was first suggested after ruling out other etiologies. Thus, a laparoscopy was promptly performed to remove the ovarian tumor. The histological endpoint revealed an ovarian teratoma. Consequently, the patient recovered completely in good health condition after 2 months in a coma status. Herein, we report an uncommon case of anti-NMDAR encephalitis associated with ovarian teratoma at our hospital, thus raising awareness of physicians.